Cranial MR Spectroscopy of Tetrahydrobiopterin Deficiency - Chien, Yin-Hsiu; Peng, Shiin-Feng; Wang, Tso-Ren; Hwu, Wuh-Liang (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Severe and progressive neurologic disease remains a problem for patients with hyperphenylalaninemia due to a deficiency of tetrahydrobiopterin (BH4), even with early diagnosis and despite treatment with BH4 and neurotransmitter precursors. Few reports have included the associated imaging characteristics. Our purpose was to describe the imaging features of BH4-deficient patients identified by neonatal screening in a Taiwanese population and to correlate the imaging features with the treatment.METHODS: This study analyzed the cases of eight BH4-deficient patients who were examined by MR imaging and MR spectroscopy. Analysis of the findings was correlated with the clinical findings.RESULTS: One patient whose intelligence quotient score was lower than those of the other seven patients experienced seizures in conjunction with central white matter signal changes on MR images and a lactate peak on MR spectroscopy. Lactate peak was revealed in another patient who had marked elevations of N-acetylaspartate:creatine and N-acetylaspartate:choline ratios. Although most patients had a higher than average N-acetylaspartate:creatine or N-acetylaspartate:choline ratio, the patient who had decreases of both ratios possessed the highest intelligence quotient scores among the eight patients. In addition, the myoinositol:choline ratio correlated positively with the average BH4 dosage (P = .027, r = 0.027) and the choline:creatine ratio correlated negatively with the average 5-hydroxytryptophan dosage (P = .035, r = −0.742).CONCLUSION: Compared with classical phenylketonuria, patients with BH4 deficiency have fewer white matter changes revealed by MR imaging but more changes revealed by MR spectroscopy. MR spectroscopy is a potential method with which to monitor the dosages of supplements used to treat this disorder. In addition, MR spectroscopy may be helpful in gaining understanding of the neurophysiological changes that occur in association with this disease.